Analysis of Value Added Tax on Creditable and Non-Creditable Input Tаx AT Сv. Karisma Jaya - Ester; Eddy Gunawan; Lenny Gurning; Gloria Cahaya Julida Hutabarat; Javerson Simamora (Universitas Muhammadiyah Palu, 2026)
This research is done in CV Karisma Jaya. The company is engaged in the sale of motorcycles. The company is located in Riau and has its headquarters in Medan, Indonesia. The purpose of this research is knowing and analyzing the system of credited input tax and not creditable input tax made by CV Karisma Jaya This research is in the form of qualitative research with a case study in CV Karisma Jaya, and the unit data used in this research analyzes the value added tax implemented in the company with creditable and non-creditable systems using the value added tax SPT report period of 2021 from CV Karisma Jaya. The data that is collected is secondary data. The results showed that the 2021 input tax reported by CV Karisma Jaya was 3,120,662,095 and after checking the 2021 input tax that should have been reported by CV Karisma Jaya was 3,087,059,273. So that there was an underpayment of 33,602,822 that had to be paid by CV Karisma Jaya in 2021.